RETRACTED: Mechanical and Tribological Performance of AlCrFeCuNi-(Vx) HEAs Synthesized via Arc Melting technique - Mpofu P; Malatji N; Shongwe M.B; Lekoadi P.M; Tlotleng M; Kanyane L.R (E3S Web of Conferences)
This proceeding volume has been retracted from the publication because we found some solid reasons to believe that it has infringed our integrity criteria and now presents a risk for our journal and scholarly science in general. Different types of malpractice are involved, in particular citation manipulation and inappropriate references. We are extremely concerned by such malpractice which considerably impacts the image of our title and our Publisher’s reputation. For further details, please refer to our publishing ethics policies. If you have any questions, please contact us at contact@webofconferences.org See the retraction notice E3S Web of Conferences 505, 00001 (2024), https://doi.org/10.1051/e3sconf/202450500001